Bacterial outer membrane vesicle biogenesis: a new mechanism and its implications - Sandro Roier; Franz G. Zingl; Fatih Cakar; Stefan Schild (Microbial Cell, 2016)
Outer membrane vesicle (OMV) release by Gram-negative bacteria has been observed and studied for decades. First considered as a by-product of cell lysis, it soon became evident that OMVs are actively secreted from the outer membrane (OM) of Gram-negative bacteria. Accordingly, these small particles (~ 10-300 nm in diameter) consist mainly of OM components like phospholipids (PLs), OM proteins, and lipopolysaccharides or lipooligosaccharides. However, OMVs may also comprise periplasmic, inner membrane, or cytoplasmic components. Since the shedding of substantial amounts of OM material represents a significant energy cost to the bacterial cell, OMV production must have some vital biological functions for Gram-negative bacteria. Indeed, intense research on that topic revealed that OMVs play important roles in bacterial physiology and pathogenesis, ranging from secretion and delivery of biomolecules (for example, toxins, DNA, or quorum sensing molecules) over stress response and biofilm formation to immunomodulation and adherence to host cells. Only recently researchers have begun to elucidate the mechanistic aspects of OMV formation, but a general mechanism for the biogenesis of these vesicles is still lacking. Here we review the findings and implications of our recent study published in Nature Communications (Roier S, et al. (2016) Nat. Commun. 7:10515), where we propose a novel and highly conserved bacterial OMV biogenesis mechanism based on PL accumulation in the outer leaflet of the OM. This mechanism might not only have important pathophysiological roles in vivo, but also represents the first general mechanism of OMV formation applicable to all Gram-negative bacteria.